Conceptual Frameworks of Real Time Flood Modelling for Improved Community Resilience - Burhanuddin M.F.; Basri H.; Sidek L.M.; Zulkhurnain S.A.; Chua L.; Irvine K.N.; Tahir W.; Khambali M.H.M.; Majid W.H.A.W.A.; Ujum E.A. (Springer Science and Business Media Deutschland GmbH, 2024)
Urbanization contributes to an increase in flood frequency and intensity, which is exacerbated by climate change. This is a phenomenon observed in both developing and industrialized countries, including Malaysia and Thailand. It is possible to lessen the devastation that natural catastrophes cause as a result of climate change by making timely and accurate predictions and being better prepared. In addition, when it comes to the general enhancement of community resilience, the utilization of effective interaction strategies between the society and the relevant agencies is an important part in the success of the endeavor. The objective of this research is to develop a real time flood modelling tool that can be put to use to lessen the likelihood of flood damage, make recommendations about climate adaptation techniques, and improve the capacity of local communities to withstand natural disasters. One case study will be conducted in Malaysia, while the other will be conducted in Thailand. These case studies will demonstrate how the developed model can reduce the impact of flooding. Two aspects of the modelling method contribute to the flexibility and resilience of the whole system which is to greatly reduce the amount of time spent on computational tasks by utilizing cloud computingandstreamlining the process of capacity growth for relevant agencies. The findings of this study will be incorporated into the formulation of a resiliency index, which will be supported by involvement with the local community and authorities. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.